Analysis of the quality of provision of physical therapy services in a children’s preschool - Prysiazhnyk, Ulyana; Vovkanych, Andriy (The Ukrainian Scientific Medical Youth Journal, 2024)
modern society is progressing very quickly. An intensive process is taking place automation and computerization of basic household items, training and development. The impact of these trends on the health of preschool and younger children is relevant schoolchildren The age period of 3-6 years is critical for the formation of correct posture and arch of the feet, because in this age range the muscular and bone systems that form the musculoskeletal system of a person. Pathological changes in the supporting of the motor apparatus are most often found in older preschool and younger children school age The main factor influencing the development of these pathologies can be consider the weakness of the muscular system, since the muscles at this age are characterized high tensile strength and, as a result, do not provide reliable fixation bones Bone tissue, in turn, is characterized by less hardness, greater plasticity, they are more easily deformed under the influence of external factors. Taking into account the listed factors, active attention should be paid to physical development children in this age period, as well as take into account all these features during development educational programs and programs of corrective and preventive orientation, which used in children’s preschools, especially in specialized ones where the child is present almost every day, as well as where it is possible to provide professional, regular and timely influence for a positive solution to the problem. Goal research: to analyze the quality of provision of physical therapy services in the nursery preschool institution of a specialized type before and after the implementation of the experimental one rehabilitation programs for children with flat-valgus foot deformity. Methods research: analysis and generalization of data from an anonymous survey of parents regarding the quality of providing physical therapy services in a specialized children’s preschool type Obtained results: the results of an anonymous survey of parents were analyzed regarding the quality of provision of physical therapy services within a children’s preschool institution specialized type (the survey was conducted separately for control and of the experimental group before and after the start of the physical therapy program completion of 12 weeks, as the experimental program was carried out during this term). The practical value of scientific work: based on an anonymous survey of parents regarding the quality of provision of physical therapy services in a children’s preschool institution of a specialized type, developed and implemented in the preschooler’s daily regime experimental program of physical therapy for children with flat-valgus deformity stop.